The new nobility : the restoration of Russia's security state and the enduring legacy of the KGB - Soldatov, Andreĭ (PublicAffairs, 2010)
In The New Nobility, two courageous Russian investigative journalists open up the closed and murky world of the Russian Federal Security Service. While Vladimir Putin has been president and prime minister of Russia, the Kremlin has deployed the security services to intimidate the political opposition, reassert the power of the state, and carry out assassinations overseas. At the same time, its agents and spies were put beyond public accountability and blessed with the prestige, benefits, and legitimacy lost since the Soviet collapse. The security services have played a central-- and often myste.